BIOETHICAL CHALLENGES IN THE USE OF NANO-MEDICINE FOR DEGENERATIVE DISEASE THERAPY - Lucas Lima; Clara Mendes; Roya Zahir; Dito Anurogo (Journal of World Future Medicine, Health and Nursing, 2026)
The emergence of nano-medicine has introduced transformative approaches for the treatment of degenerative diseases, including Parkinson’s, Alzheimer’s, and osteoarthritis. These technologies enable targeted drug delivery, enhanced bioavailability, and improved therapeutic precision. Despite clinical potential, ethical challenges related to patient comprehension, informed consent, and long-term safety remain underexplored, particularly for vulnerable populations affected by cognitive decline. Understanding these challenges is critical for aligning technological innovation with bioethical principles. This study aims to investigate the bioethical issues arising from the use of nano-medicine in degenerative disease therapy and to identify strategies that enhance ethical implementation in clinical practice. The research further seeks to develop a conceptual framework to guide ethical decision-making in emerging medical technologies. A qualitative exploratory design was employed, including fifteen participants comprising clinicians, patients, and regulatory authorities. Data were collected through semi-structured interviews, direct observation of clinical interactions, and document analysis of protocols and consent forms. Thematic coding and triangulation were applied to elucidate patterns in ethical practices, communication strategies, and institutional oversight. Findings indicate that patient comprehension varies significantly with age and cognitive status, while clinician strategies and institutional protocols influence ethical adherence. Iterative consent processes and technological support enhance transparency, autonomy, and responsible clinical practice.